The angiotensin receptor neprilysin inhibitor LCZ696 attenuates renal fibrosis via ASK1/JNK/p38 MAPK-mediated apoptosis in unilateral ureteral obstruction. - Jun Ding; Sheng Cui; Song Yu Li; Lin Yan Cui; Qi Yan Nan; Xue Jing Lin; Mei Ying Xuan; Jian Jin; Shang Guo Piao; Yu Ji Jiang; Hai Lan Zheng; Ji Zhe Jin; et al. (PLoS ONE, 2023)
The angiotensin receptor neprilysin inhibitor LCZ696 affords superior cardioprotection and renoprotection compared with renin-angiotensin blockade monotherapy, but the underlying mechanisms remain elusive. Herein, we evaluated whether LCZ696 attenuates renal fibrosis by inhibiting ASK1/JNK/p38 mitogen-activated protein kinase (MAPK)-mediated apoptosis in a rat model of unilateral ureteral obstruction (UUO) and in vitro. Rats with UUO were treated daily for 7 days with LCZ696, valsartan, or the selective ATP competitive inhibitor of apoptosis signal-regulating kinase 1 (ASK1), GS-444217. The effects of LCZ696 on renal injury were examined by assessing the histopathology, oxidative stress, intracellular organelles, apoptotic cell death, and MAPK pathways. H2O2-exposed human kidney 2 (HK-2) cells were also examined. LCZ696 and valsartan treatment significantly attenuated renal fibrosis caused by UUO, and this was paralleled by downregulation of proinflammatory cytokines and decreased inflammatory cell influx. Intriguingly, LCZ696 had stronger effects on renal fibrosis and inflammation than valsartan. UUO-induced oxidative stress triggered mitochondrial destruction and endoplasmic reticulum stress, which resulted in apoptotic cell death; these effects were reversed by LCZ696. Both GS-444217 and LCZ696 hampered the expression of death-associated ASK1/JNK/p38 MAPKs. In H2O2-treated HK-2 cells, LCZ696 and GS-444217 increased cell viability but decreased the production of intracellular reactive oxygen species and MitoSOX and apoptotic cell death. Both agents also deactivated H2O2-stimulated activation of ASK1/JNK/p38 MAPKs. These findings suggest that LCZ696 protects against UUO-induced renal fibrosis by inhibiting ASK1/JNK/p38 MAPK-mediated apoptosis.